How strategic agility effects strategy implementation in servitizing companies? - Kotkova, Kristyna (My University, 2018)
As a dynamic meta-capability, strategic agility is recognized as a lever for a holistic strategic change, enabling companies to learn, develop and create new capabilities and find and balance the right fit between the external forces and the company’s strategy, structure and processes. Strategic agility heavily focuses on understanding external stimuli (market forces, customers’ needs and their value creation), which is a shared element with one of the currently most discussed strategic transformation of manufacturers, servitization. The aim of this qualitative thesis is to explore the role of strategic agility in servitization and shed some light on how strategic agility effects strategy implementation in servitizing companies. The conceptual framework is built on strategic agility, strategy implementation and servitization literature, which allows deeper understanding of strategic agility itself and its specific form in an early stage servitizing company. The empirical part of the study was conducted through an in-depth revelatory single-case study, by using semi-structured interviews. The data were collected from eight knowledgeable informants, who were actively involved with the strategy implementation; however, who worked in different teams and countries, thus provided different viewpoints on the same phenomenon. As a result, the final concept of strategic agility in servitization comprise of four main dimensions: sensitivity, fluidity, leadership and continuity, with fifteen embedded capabilities. The findings indicate that strengthening strategic agility in servitization process could mitigate challenges connected to it, such as the scarcity of resources, strategic misfit, cultural readiness and employee commitment. It supports the company’s transformation through the holistic transition process. Moreover, this study presents that thought the dimensions of strategic agility are irreplaceable, the mix of embedded capabilities varies according to a specific transformation process.
Keywords: Strategic agility; Strategic agility dimensions; Dynamic capabilities; Servitization; Strategy implementation; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|